If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -51 = 0 Reorder the terms: -51 + 3x = 0 Solving -51 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '51' to each side of the equation. -51 + 51 + 3x = 0 + 51 Combine like terms: -51 + 51 = 0 0 + 3x = 0 + 51 3x = 0 + 51 Combine like terms: 0 + 51 = 51 3x = 51 Divide each side by '3'. x = 17 Simplifying x = 17
| 2x+3Y=-16 | | z^2-12z-270=0 | | 2x^2-7x=4 | | 2x+x+16+x+16=200 | | 2x+x+16=200 | | 3x+1=292 | | 3m+mn+18+6n= | | 76-3x=9x | | 25.8+17.3-4.2x=65.1 | | 7x+20+9x=47+5x+61 | | 7(x+2)-3(x+1)=5(x-6)-8(2x-6) | | 3g+7=-6-56 | | 30+1.95x=7.95x | | ln(-2x)=7 | | -5+32x^2-24x^2+44=6x | | x*9+12=x*4+162 | | 25-x-19=26-5x-6x | | 7x^7-56x^6+42x^5= | | 165-7x=20x+15 | | 10-10x=118-38x | | 2x-x+8x= | | 179-5x=6x+14 | | 9(x-3)+8(x+6)=4(8-7x) | | 0.1(x+100)+0.1x=1 | | -1*[-2]=x | | -36-2x+9x=3x+12 | | 5(t-2)-3t=4(2+4)-9 | | 4(2x+9)=20 | | 8a^2+4a= | | 9+n=2n-4 | | 9-10x=94-45x | | (x+2)(2x-3)=0 |